Serum β-klotho is a potential biomarker for diagnosing alcoholic liver disease and differentiating from nonalcoholic fatty liver disease - Chengmei Fang; Xin Miao; Chuyan Peng; Zhenguo Xie; Fuzhen Zhao; Tian Chen; Wenjin Zhang; Xiaofei Bi; Xuan An; Guicheng Wu (PeerJ)
Background Alcoholic liver disease (ALD), with the control of infectious liver disease and the improvement in living standards, is emerging as a significant liver disease posing a threat to public health. Besides, ALD often overlaps or coexists with nonalcoholic fatty liver disease (NAFLD), however, due to the lack of specific non-invasive biomarkers and the fact that drinkers’ self-reported alcohol consumption is often concealed, the identification of ALD and NAFLD is sometimes not easy. This study aims to explore a new specific serum biomarker to more easily diagnose ALD and differentiate it from NAFLD. Subjects and Methods A total of 204 serum samples were collected, including 70 from ALD patients, 68 from NAFLD patients and 66 from healthy controls (HC). Serum β-klotho (sKLB) levels were measured using the enzyme-linked immunosorbent assay (ELISA). The diagnostic performance of potential biomarkers was evaluated using the area under the receive operating characteristic curve (AUROC). Results The levels of sKLB were significantly elevated (1,332.12 (410.40, 2,687.00) pg/mL, p < 0.001) in ALD patients and significantly reduced in NAFLD patients (47.82 (32.76, 77.11) pg/mL, p = 0.018) compared to the healthy controls. The AUROC for sKLB in diagnosing ALD is 0.927, which was higher than that for the aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio (0.672) and γ-glutamyl transpeptidase (GGT) (0.891). The combined AUROC for sKLB + AST/ALT, sKLB + GGT, and AST/ALT ratio + GGT in diagnosing ALD were 0.924, 0.967 and 0.917, respectively. Conclusion sKLB is a potential biomarker for diagnosing ALD, and may aid in differentiating between ALD and NAFLD, when combined with GGT, sKLB offers enhanced diagnostic sensitivity and specificity for ALD.